Peningkatan Kemampuan Siswa OSIS dalam Pengelolaan Media Sosial Sekolah Melalui Pendampingan Konten Kreatif di SMAN 1 Penebel - Ni Wayan Nanik Suaryani Taro Putri; Eka Grana Aristyana Dewi; I Putu Arya Januartha; Made Diandra Maharani; I Nyoman Ganendra Maheswara; Ni Kadek Puspa Tirani Dewi; I Made Adi Nugraha (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
Social media is one of the most effective promotional tools today. At SMAN 1 Penebel, student organization members use social media to promote their school, but many still lack the skills to create engaging content. This community service activity aims to improve students’ ability to use social media as a promotional tool. The activity uses a Design Thinking approach with five stages: empathize, define, ideate, prototype, and test. In the empathize stage, interviews were conducted with students and teachers to identify existing issues. In the define stage, a vote was held to select one main problem. During ideation, team members proposed solution ideas. In the prototype stage, a prototype was designed as a basis for implementation, and in the test stage, it was validated. The implementation was carried out through practice-based training, where students were directly taught how to create content. Evaluation results from questionnaires showed that most students responded “fairly understand” and “fully understand” with the highest understanding in video editing applications and scriptwriting. It can be concluded that the majority of OSIS students improved their ability to use social media as a school promotional medium.